2005
DOI: 10.2108/zsj.22.343
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny and Evolution of Butterflies of the Genus Parnassius: Inferences from Mitochondrial 16S and ND1 Sequences

Abstract: -Phylogenetic relationships among species of the genus Parnassius and its related taxa were analyzed by comparing nucleotide sequences of mitochondrial 16S ribosomal RNA (504 sites) and NADHdehydrogenase subunit 1 (469 sites). In the phylogenetic trees, Parnassius was found to be most closely related to Hypermnestra helios , whereas Archon apollinus , which has been classified in the tribe Parnassiini together with Parnassius and Hypermnestra , was more closely related to members of the tribe Zerynthiini. With… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 16 publications
5
16
2
Order By: Relevance
“…Further study adding data of the 16S and ND1 sequences, as well as more detailed statistical analyses, confirmed the result mentioned above (Katoh et al, 2005). Nazari and his colleagues reported detailed molecular systematic studies using a large set of data of five mtDNA loci (COI, COII, ND5, ND1, 16S) together with two nuclear DNA loci (EF1α and wg).…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…Further study adding data of the 16S and ND1 sequences, as well as more detailed statistical analyses, confirmed the result mentioned above (Katoh et al, 2005). Nazari and his colleagues reported detailed molecular systematic studies using a large set of data of five mtDNA loci (COI, COII, ND5, ND1, 16S) together with two nuclear DNA loci (EF1α and wg).…”
Section: Introductionsupporting
confidence: 67%
“…Omoto et al (2004) firstly indicated that the tribe Parnassiini (Parnassius, Hypermnestra and Archon) is not a monophyletic group. This relation was confirmed by Katoh et al (2005), Nazari et al (2007) and Michel et al (2008).…”
Section: Diversity Of the Sphragis Form In Clade VIsupporting
confidence: 53%
“…Omoto et al (2004) showed that Hypermnestra Ménétriès, 1848 is more closely related to Parnassius than to Archon Hübner, 1822, and they divided Parnassius into eight groups. Katoh et al (2005) made the same conclusions. and showed that Hypermnestra and Parnassius form sister groups.…”
Section: Introductionsupporting
confidence: 61%
“…The species is distributed also in Afghanistan, Pakistan, Tibet and India; however, it is not easy to get fresh material from these countries. We did use several samples from these locations to see how they are connected to our delimited area and we included samples of K. charltonius from GenBank (mainly from publications of Omoto et al 2004;Katoh et al 2005;Michel et al 2008;Churkin and Michel 2014; Tables 2, 3) and also other taxa as outgroups and for calibration points (Hypermnestra helios (Nickerl, 1846), Koramius stoliczkanus (Felder & Felder, 1865), K. acdestis (Grum-Grshimailo, 1891), K. augustus (Fruhstorfer, 1903), K. imperator (Oberthür, 1883), K. inopinatus (Kotzsch, 1940), K. autocrator (Avinov, 1913), K. loxias (Püngeler, 1901)) (Table 4). To overcome the problem with potentially incorrect collecting information for the taxonomic part of our work, in cases of uncertainty we restricted our data to the type material and we omitted material from GenBank.…”
Section: Specimen Samplingmentioning
confidence: 99%
“…1C) confirms the monophyletic status of the species and the close relatedness to the P. phoebus–P. bremeri complex (Omoto et al ., 2004; Katoh et al ., 2005), with an average patristic nucleotide distance ( P. apollo vs. P. phebus–P. bremeri ) of 0.034 (SD = 0.004).…”
Section: Resultsmentioning
confidence: 99%